Effect on growing of Bali cattle with difference age raised in cages - Harapin Hafid (Talenta Publisher, 2020)
The purpose of this study was to obtain information on the influence of age differences on the growth of Bali cattle that are traditionally reared in cages. The number of cattle used were 9 heads. During the study, individual cages were used. This study had a randomized block design with three ranges of body weight as a group. The treatment in this study was the difference in the age of cattle, which consisted of cattle aged 1 year (I1), age 2 years (I2) and 3 years (I3). The results showed that the difference in the age of the cattle had no significant effect (P> 0.05) on the dry matter consumption of feed, daily body weight gain and the conversion of Bali cattle feed traditionally reared in pens. However, there is a tendency that cattle aged 1 year have better growth and efficiency in using feed than cattle aged 2 and 3 years. It can be concluded that raising cattle at 1 year of age results in more efficient growth than cattle at 2 and 3 years. However, further testing needs to be done with a higher number of cattle and a wider range of body weight.